Selective accumulation of ALA-induced PpIX and photodynamic effect in chemically induced hepatocellular carcinoma - Otake, M (Nature Publishing Group, 2003)
The possibility of 5-aminolaevulinic acid-based photodynamic therapy (ALA-PDT) for liver cancer was investigated using a chemically induced hepatocellular carcinoma (HCC) model. Endogenously synthesised protoporphyrin IX (PpIX) following the administration of ALA is an effective photosensitiser for PDT. We determined the fluorescence intensity of PpIX in HCC and nontumoral tissue in the liver. 5-Aminolaevulinic acid was intravenously injected to male Fisher rats with HCC at a dose of 500 mg kg(−1), and the fluorescence intensity in each tissue sample excised from liver was measured with a spectrofluorometer at 1, 3 and 6 h after administration. Fluorescence intensity was at a peak of 3 h after administration in both HCC and nontumoral tissue. The accumulation of PpIX in HCC was higher than that in the nontumoral tissue at 1 h (P<0.001) and 3 h (P<0.05) after ALA administration. Based on these results, PDT was performed on HCC at 3 h after 500 mg kg(−1) ALA administration before laser irradiation of 30 J per tumour. Antitumour effect was more evident in HCC than in the nontumoral tissue surrounding HCC. These findings suggest the possibility to detect HCC by fluorescence and to treat HCC by light.